Validation of Multi-epitope Peptides Encapsulated in PLGA Nanoparticles Against Influenza A Virus - Heng, Wen Tzuen *; Lim, Hui Xuan *; Tan, Kuan Onn *; Poh, Chit Laa * (Springer, 2023)
Background: Influenza is a highly contagious respiratory disease which poses a serious threat to public health globally, causing severe diseases in 3-5 million humans and resulting in 650,000 deaths annually. The current licensed seasonal influenza vaccines lacked cross-reactivity against novel emerging influenza strains as they conferred limited neutralising capabilities. To address the issue, we designed a multi-epitope peptide-based vaccine delivered by the self-adjuvanting PLGA nanoparticles against influenza infections.